A robust timing recovery algorithm with frequency offset for MIL-STD SOQPSK - Yingying Dong; Qifeng Wang; Zhengguang Xu (2016 11th International Symposium on Antennas, Propagation and EM Theory (ISAPE), 2016)
A robust timing recovery algorithm for military standard (MIL-STD) shaped-offset quadrature phase-shift keying (SOQPSK) is presented and this scheme can be used in the signal with frequency offset. The new algorithm is based on the correlation calculation, and the timing offset information is extracted by the absolution operation to the correlation function. The theoretical analysis and the simulation result both show that the provided scheme can work well to the MIL-STD SOQPSK signal with frequency offset.